Social Interaction between Siblings in Families Who Have Children with Autism Spectrum Disorder - Parirak, Angel Meylia; Kristinawati, Wahyuni; Adiyanti, Maria Goretti (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Individuals with Autism Spectrum Disorder (ASD) are characterized by deficits in social interaction such as in initiating, developing, and maintaining it. This ultimately affects the dynamics of social interaction between siblings. This study aims to analyze the dynamics of interaction and contributing factors. Participants consisted of 4 people, namely 2 pairs of siblings from 2 families (1 sibling with ASD and 1 sibling without ASD from each family). The method used was qualitative with a phenomenological approach. Data collection was carried out through interviews and observations of all participants and parents. The results of the study showed that there were actions that influenced each other's behavior in daily interactions due to various contributing factors including gender, birth order, age, sibling behavior, and parental roles. Interactions between siblings, one of whom had ASD, ultimately still occurred even though more dynamics and obstacles were found, but harmonious interactions or conflicts that occurred could be strengthened or reduced. This depends on the approach and support from those closest to them in helping children with ASD and their siblings respond to and manage situations in daily interactions. These findings indicate the importance of exploring the role of siblings, which is often overlooked, even though they are the closest figures. Sibling interactions can improve social skills, strengthen emotional bonds, and enhance well-being for children with ASD and their siblings. This review suggests further exploration of similar topics, from multiple perspectives, to enrich further literature.